Construção e validação de um website educativo para promoção da amamentação e prevenção de hábitos bucais deletérios - Batista, Risolinda Rodolfo de Sá (2016)
Breastfeeding has advantages that have been known and diffused in society since the earliest times. It is understood that it can interfere in the quality of life of the child and the family and its absence can lead to emotional, nutritional and cognitive problems, besides stimulating the installation of non-nutritive sucking habits and, consequently, the establishment of dental malocclusion And disturbances in the child's orofacial growth and development. In this sense, the health professional is important for stimulating breastfeeding, since it can prevent early weaning and contribute to improving the health conditions of the child. The aim of this study was to develop and validate an educational website for breastfeeding and oral health, linking technology and health to the benefit of the community. The aim of this study was to promote breastfeeding practices and prevent the establishment of deleterious oral habits. It was a methodological study, which was developed by Falkembach (2005), which is composed of five phases: analysis and planning, modeling, implementation, evaluation and distribution. Therefore, the "Amor Além do Seio" website was created, which presented the following sections and subsections: Home, Breastfeeding (breastfeeding and its benefits, possible difficulties), Oral Health (oral health and breastfeeding, deleterious habits, malocclusion, Oral hygiene) and Learn More. The validation step was performed through the collection of data with six judges of content and three of appearance. The results were evaluated according to the Content Validity Index (CVI), with a cutoff point of 0.80. The website presented IVC content of 0.95 and IVC of appearance of 0.90, being considered approved by the judges. Before the suggestions and contributions, from the validation process, the website has undergone changes in order to make it more attractive and easy to navigate. It is concluded that the educational website "Love Beyond the Breast" becomes a means of disseminating knowledge about breastfeeding and its relationship with the child's orofacial development, stimulating healthier practices alongside the mother-child-family trinomial. Pedagogical and interactive way. In addition, this educational material, reliable and valid, extends the range of action of the Family Health Strategy, expanding the role of the dental surgeon in the area of ​​health education and lifelong education.